Chagas' infection in university students of Santa Cruz de la Sierra, Bolivia. A serologic-electrocardiographic study - Gianella, A. (1994)
In order to learn the prevalence of Chagas' infection among students from Santa Cruz de la Sierra's universities, a random sample of 372 new students was drawn. All participants have had electrocardiograms (EKG) and serologic analysis (IHAT). 64/372 (17.2%) had serologic evidence of Chagas' infection, and from those, 10/64 (15.6%) had some EKG alterations. Among students presenting negative serologic test, 31/308 (10.1%) had EKG alterations. There was no statistical association between Chagas' infection and EKG alterations (X2=1.67, p=0.2). There was a positive association between Chagas' infection and intraventricular conduction defects and this association was higher among the students of 19 years of age or less (O.R. 10.4, p